Genomic Characterization of Strains From a Cluster of Infant Botulism Type A in a Small Town in Colorado, United States - Gladney, Lori; Halpin, Jessica L.; Lúquez, Carolina (Frontiers in Microbiology, 2021)
Three cases of infant botulism were reported in a small Colorado town between 1981 and 1984. The first two cases occurred in 1981, six months apart, and the third case occurred in 1984. Clostridium botulinum type A was isolated from stool of all three case patients and from environmental samples of the patient’s homes. An epidemiological investigation and follow-up study were conducted from 1981 to 1986 and concluded the cases were likely related. In this study, we sought to determine if the C. botulinum type A clinical isolates were related to each other and to isolates obtained from environmental samples. We performed whole genome sequencing (WGS) for seventeen isolates associated with this potential cluster of infant botulism. Fifteen isolates were confirmed to be C. botulinum type A(B) and contained botulinum toxin gene subtypes A1 and B5 by WGS; these strains formed a monophyletic cluster in a phylogeny and were considered closely related to each other (0-18 high-quality SNPs), but distinct from other C. botulinum type A(B) in Colorado and elsewhere in the US. Results of our study suggest that the three infant botulism cases could have represented a cluster due to a C. botulinum type A(B) strain present in the environment.